Cytochemical characterization of gill and hepatopancreatic cells of the crab Ucides cordatus (Crustacea, Brachyura) validated by cell metal transport - Priscila Ortega; Rudney A. Santos; Patrícia Lacouth; Enrique E. Rozas; Márcio R. Custódio; Flavia Pinheiro Zanotto (Iheringia: Série Zoologia, 2014)
Ucides cordatus (Linnaeus, 1763) is a hypo-hyper-regulating mangrove crab possessing gills for respiratory and osmoregulatory processes, separated in anterior and posterior sections. They also have hepatopancreas, which is responsible for digestion and absorption of nutrients and detoxification of toxic metals. Each of these organs has specific cells that are important for in vitro studies in cell biology, ion and toxic metals transport. In order to study and characterize cells from gills and hepatopancreas, both were separated using a Sucrose Gradient (SG) from 10 to 40% and cells in each gradient were characterized using the vital mitochondrial dye DASPEI (2-(4-dimethylaminostyryl)-N- ethylpyridinium iodide) and Trichrome Mallory's stain. Both in 20 and 40% SG for gill cells and 30% SG for hepatopancreatic cells, a greater number of cells were colored with DASPEI, indicating a larger number of mitochondria in these cells. It is concluded that the gill cells present in 20% and 40% SG are Thin cells, responsible for respiratory processes and Ionocytes responsible for ion transport, respectively. For hepatopancreatic cells, the 30% SG is composed of Fibrillar cells that possess larger number of membrane ion and nutrient transporters. Moreover, the transport of toxic metal cadmium (Cd) by isolated hepatopancreatic cells was performed as a way of following cell physiological integrity after cell separation and to study differences in transport among the cells. All hepatopancreatic cells were able to transport Cd. These findings are the first step for further work on isolated cells of these important exchange epithelia of crabs, using a simple separation method and to further develop successful in vitro cell culture in crabs.